Stratigraphy and Structural Style of the Maghrebides Belt Foreland: Souk Ahras Sellaoua Unit Case (External Domain, NE Algeria) - Abdallah CHABBI; Asma Chermiti; Stéphane Brusset (My University, 2022)
The Sellaoua Unit is part of the foreland of the Maghrebides belt in northeastern Algeria and develops in the footwall of Tellian and Numidian thrust sheets. Detailed geological mapping of Souk Ahras Sellaoua Unit (North–East of Algeria) supported by micro-paleontological and structural data allows us to reappraise the stratigraphy and the structural style of such area and characterize its relationship with the northern adjacent thrust sheets. Data were collected from sampling and observations along with four profiles for biostratigraphic study and five for structural constructions. The obtained results show that the Sellaoua Unit of the Souk Ahras area is made of carbonate marine formations ranging from Turonian to Paleocene uncomfortably overlain by detrital Miocene strata. Complex thrust systems have occurred during the Tertiary until the middle Miocene.